Intake of Fibre-Associated Foods and Texture Preferences in Relation to Weight Status Among 9–12 Years Old Children in 6 European Countries - Hörmann-Wallner, Marlies; Krause, Raphaela; Alfaro, Begoña; Jilani, Hannah; Laureati, Monica; Almli, Valérie L.; Sandell, Mari; Sandvik, Pernilla; Zeinstra, Gertrude G.; Methven, Lisa (Frontiers in Nutrition, 2021)
Plant foods, rich in fibre, can offer textures that children find difficult to orally manipulate, resulting in low preferences but are important for a healthy diet and prevention of overweight in children. Our aim was to investigate preferences for food texture, intake of fibre-associated foods and the relation to BMI. 330 European children (9-12 years, 54% female) indicated their texture preferences using the Child-Food-Texture-Preference- Questionnaire (CFTPQ), and their parents responded on fibre-associated food consumption and anthropometric information. BMI was significantly lower for children with higher intake of wholegrain alternatives of common foods; in addition to being significantly influenced by country and the wearing of a dental brace. Overall BMI-for-age-percentiles (BMI_pct) were negatively associated with the consumption of wholegrain cereals, white pasta and wholemeal products and positively associated with the intake of legumes and white biscuits. In males, BMI_pct were negatively associated with wholegrain products and dried fruits, and in females, positively with legume consumption. A few country-related associations were found for BMI_pct and wholegrain biscuits, seeds and nuts and refined products. No overall correlation was found between BMI_pct and the texture preference of soft/hard foods by CFTPQ, except in Austria. We conclude that this study revealed evidence of a connection between fibre-associated foods and children`s BMI at a cross-cultural level and that sex is an important determinant of fibre-associated food intake and the development of overweight in childhood.